LEARNING PATTERNS AND ACADEMIC ENGAGEMENT OF KUWAITI UNDERGRADUATES - Seitaj, Laureta (PEOPLE: International Journal of Social Sciences, 2019)
This study was aimed to analyze the relationship between learning patterns, academic engagement, and GPA. The participants were 81 undergraduates from a private Engineering and Business College in Kuwait who were asked to complete the Inventory of Learning Styles (ILS) and Student Engagement Inventory- College Version (SEI-C). The data were analyzed via correlation analysis, using SPSS statistical package. The results showed that student’s learning patterns were associated with student’s type of engagement to learn. In this respect, the Teacher-Student Relationship (TSR) was positively related to Meaning- and Reproduction-Directed pattern. Control and Relevance of Schoolwork (CRS) and Future Goals (FGA) were related to all patterns, except for the Undirected pattern (UD). Conversely, UD, and RD pattern were related to Peer Support (PSL). Finally, the GPA was related to the Application-Directed pattern, only. Furthermore, the results from a cultural perspective are discussed.